1993
DOI: 10.1038/366565a0
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor needs two homologous domains of the & beta;-subunit for activation by GABA but not by pentobarbital

Abstract: The predominant inhibitory neurotransmitter of the brain, GABA (gamma-aminobutyric acid), activates chloride-selective ion pores integral to the receptor complex. Subunits comprising the presumed hetero-pentameric GABA channel have been cloned, but little information is available on the domains important for activation. Rat wild-type or mutated alpha 1-, beta 2- and gamma 2-subunits (designated alpha, beta and gamma) were coexpressed in Xenopus oocytes and examined electrophysiologically. We report here the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
361
2
3

Year Published

1995
1995
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(390 citation statements)
references
References 29 publications
24
361
2
3
Order By: Relevance
“…Mutagenesis studies have identified amino acids within the N-terminal domains of both GABA A receptor ␣ and ␤ subunits that are involved in the formation of GABA-binding sites, leading to the hypothesis that the GABA-binding site is located at the interface between the ␣ and ␤ subunits (Amin and Weiss 1993;Smith and Olsen, 1995). Interestingly, residues between 57 and 69 within ␣1 have previously been implicated in the binding of receptor agonists (Smith and Olsen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies have identified amino acids within the N-terminal domains of both GABA A receptor ␣ and ␤ subunits that are involved in the formation of GABA-binding sites, leading to the hypothesis that the GABA-binding site is located at the interface between the ␣ and ␤ subunits (Amin and Weiss 1993;Smith and Olsen, 1995). Interestingly, residues between 57 and 69 within ␣1 have previously been implicated in the binding of receptor agonists (Smith and Olsen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to benzodiazepines, barbiturates also stimulate inhibitory GABA A receptors in the brain. However, barbiturates appear to augment benzodiazepines' efficacy at the GABA A receptor (35). In addition, barbiturates can also inhibit stimulatory glutamate receptors, which are upregulated in alcohol withdrawal (36 -38).…”
Section: Discussionmentioning
confidence: 99%
“…5); thus, it is not surprising that changing it to serine or alanine in the 5-HT 3 native aromatic, phenylalanine, resulted in changed functional receptor characteristics (an ϳ10-fold increase in EC 50 ) but not in binding affinity (K d not significantly different from WT), thus supporting a role for the hydroxyl group in receptor gating. Extensive site-directed mutagenesis of the residue at this location has shown that it is important in the nACh receptor (39), the ␥-aminobutyric acid A receptor (40), and the glycine receptor (41), although there is some debate as to whether it affects the binding affinity (42) or the gating constant (43). The binding of dTC and its analogues to the nACh receptor has been particularly well studied, and there was evidence that these compounds might interact via cation-interactions with Tyr 198 (35).…”
Section: Discussionmentioning
confidence: 99%